Barriers of Ukrainian refugees and migrants in accessing German healthcare - Karina Davitian; Peter Noack; Katharina Eckstein; Jutta Hübner; Emadaldin Ahmadi (BMC Health Services Research, 2024)
Abstract Background This study focused on Ukrainian refugees and migrants, a population that, with an ongoing war, is expected to grow in Germany. Over 1 million Ukrainians with exceptional legal status and access to public insurance in Germany significantly burden governmental services, especially German healthcare. It is thus essential to facilitate their integration into the healthcare system and ensure its proper usage. Identifying the obstacles Ukrainian refugees and migrants encounter while accessing healthcare services is crucial to ease their integration. Methods A qualitative study was conducted from February 2023 to April 2023. Thirty semi-structured interviews were performed with Ukrainian migrants and refugees. The interviews were transcribed verbatim, organized, and categorized. Thematic analysis was performed to identify barriers related to the use of German healthcare services. To assess possible differences in the experiences of Ukrainian refugees and migrants, the responses of these two groups for each topic were analysed separately. Results Ukrainian migrants and refugees experience similar barriers while accessing German healthcare services. Predominantly, language barriers and a lack of understanding of the German healthcare system posed the main barriers in both groups. Additionally, structural challenges, such as differences in referral processes, appointment scheduling, and consultation duration, presented further challenges. Conclusion This research study emphasizes the importance of addressing cultural and structural barriers to improve healthcare accessibility and utilization for Ukrainian refugees and migrants in Germany to better facilitate their integration into the healthcare system.